EFEKTIVITAS PENGGUNAAN BUILDING BLOCKS “LEGO” UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA DINI - Ika Apriati Widya Puteri; Marselina Huring (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2020)
The purpose of this research is to know the effectiveness of building blocks "Lego" to enhance the visual ability of the motor in early childhood. This research uses the Pre Experimental Design method or is also commonly known as Quasi Experiment. The form of experimental design used is The One Group Pretest-posttest Design. The implementation of this research uses single-group design with Pretests and Posttest conducted by conducting experiments on one group, without the use of comparative groups. The subject of this study was children who participated in a Lego course in Robokidz Samarinda for 3 people, aged 5-6 years. Measuring instruments In this study use the child's fine motor Development observation sheet and semi-structured interviews with teachers. The results showed that the use of building blocks "Lego" does not improve the fine motor capability of early childhood significantly (z =-1,414, p = 0157). However, the subject shows a trend for the improvement of fine motor capability indicated by the increase in the child's fine motor proficiency score.